Unveiling quality, clinical, and financial Impacts of Pulmonary Tuberculosis Clinical Pathway Implementation in Magelang Public Hospital, Indonesia: 10.55131/jphd/2024/220120 - Dhaniaputri, Andriyani; Arini, Merita (Journal of Public Health and Development, 2024)
Tuberculosis (TB) is a popular endemic disease in Indonesia with increased risk outcomes. The clinical pathway (CP) is crucial to enhancing healthcare services and resource efficiency despite discrepancies in service variability reduction, clinical outcomes improvement, and cost saving. Therefore, this study aimed to assess pulmonary TB CP and evaluate its impacts on clinical and financial results, as well as barriers to implementation at Tidar Hospital in Magelang, Indonesia. A sequential explanatory mixed-method design was used from July 2022 to January 2023. The study began with a retrospective analysis of medical records of TB patients (total sampling, n=92). In-depth interviews (IDIs) were conducted with healthcare workers including the quality and medical committee, case manager, CP team, inpatient and non-inpatient nursing sub-coordinators, and pulmonary specialists. In addition, eight multidiscipline healthcare professionals attended the focus group discussions (FGDs). The audio recordings were transcripted verbatim and subjected to thematic analysis. The results showed that the quality and content of CP based on TB evaluation using the Integrated Clinical Pathway Assessment Tool (ICPAT) was 62.6%. Four themes were obtained: 1) CP implementation techniques, 2) supportive factors in the success of CP, 3) organization support in CP implementation, and 4) TB patient outcomes. Furthermore, procedure compliance after CP implementation was 33%. There were no significant differences in the length of stay (p=0.77), diagnosis investigation and therapy appropriateness (100%), mortality (4 vs 3 patients; p=0.589), and cost efficiency with an average cost of care (Rp 6.994.508,- vs Rp 5.521.091,-; p=0.083) before and after CP implementation. Readmission rates were low before and after deployment (1 vs. 2 patients). This study found no significant clinical or financial benefits in TB CP implementation. These results imply the need for hospital leadership and a multidisciplinary team to overcome CP implementation hurdles.